Diseño de una máquina aglutinadora para reciclaje de bolsas plásticas de polietileno de baja densidad (2016)
This project began with an investigation of polyethylene of low physical density of the bags to be recycled, with all information gathered different alternative solutions to the problem were raised and through an evaluation system the most convenient alternative was chosen the conceptual design machine consists of a horizontal wrenching system and a binder system vertically with belt drive, the structural components were analyzed by the finite element method, production drawings, installation and maintenance, financial evaluation and environmental impact of the project were delivered